Pentafluorophenyl Substitution of Natural Di(indol‐3‐yl)methane Strongly Enhances Growth Inhibition and Apoptosis Induction in Various Cancer Cell Lines. Issue 4 (19th March 2019) - Ahmad, Aamir; Dandawate, Prasad; Schruefer, Sebastian; Padhye, Subhash; Sarkar, Fazlul H.; Schobert, Rainer; Biersack, Bernhard
Abstract: Di(indol‐3‐yl)methane (=3, 3′‐methanediyldi(1 H ‐indole), DIM, 1 ) is a known weakly antitumoral compound formed by digestion of indole‐3‐carbinol (=1 H ‐indol‐3‐ylmethanol), an ingredient of various Brassica vegetables. Out of a series of nine fluoroaryl derivatives of 1, three pentafluorophenyl derivatives 2c, 2h, and 2i were identified that exhibited a two to five times greater anti‐proliferative effect and an increased apoptosis induction when compared with 1 in the following carcinoma cell lines: BxPC‐3 pancreas, LNCaP prostate, C4‐2B prostate, PC3 prostate and the triple‐negative MDA‐MB‐231 breast carcinoma. Compound 2h was particularly efficacious against androgen‐refractory C4‐2B prostate cancer cells (IC50 =6.4 μm ) and 2i against androgen‐responsive LNCaP cells (IC50 =6.2 μm ). In addition, 2c and 2h exhibited distinct activity in three cancer cell lines resistant to 1 . Abstract :